2014
DOI: 10.1002/phar.1426
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐Mediated Rejection in Kidney Transplantation: A Review of Pathophysiology, Diagnosis, and Treatment Options

Abstract: Antibody-mediated rejection (AMR), also known as B-cell-mediated or humoral rejection, is a significant complication after kidney transplantation that carries a poor prognosis. Although fewer than 10% of kidney transplant patients experience AMR, as many as 30% of these patients experience graft loss as a consequence. Although AMR is mediated by antibodies against an allograft and results in histologic changes in allograft vasculature that differ from cellular rejection, it has not been recognized as a separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 63 publications
2
82
0
5
Order By: Relevance
“…of multiple myeloma, a plasma cell tumor, and has also been used for kidney transplant rejection with some success [54].…”
mentioning
confidence: 99%
“…of multiple myeloma, a plasma cell tumor, and has also been used for kidney transplant rejection with some success [54].…”
mentioning
confidence: 99%
“…Antibody-secreting plasma cells do not express CD20 and would not be expected to have any response to anti-CD20. 48 One systematic review and meta-analysis of 10 small retrospective or nonrandomized trials evaluating use of rituximab in AMR suggested that use of this agent is associated with improved graft outcome; however, the favorable effect was driven by 2 larger studies included in the analysis. 49 A systematic review of 21 studies (2 randomized controlled trials and 19 retrospective cohort studies) did not support the use of rituximab in desensitization in highly sensitized recipients.…”
Section: Anti-cd20mentioning
confidence: 99%
“…En ambas vías de alorreconocimiento están implicados el complejo mayor de histocompatibilidad (CMH), los distintos subgrupos de células T (TH1 y TH2) y la coestimulación (45,49). Los anticuerpos que pueden mediar el rechazo de tipo humoral son aquellos dirigidos contra moléculas HLA, antígenos de la célula endotelial y antígenos del complejo ABO en células endoteliales y eritrocitos (50). Generalmente, el rechazo humoral (o rechazo mediado por anticuerpos) se manifiesta como hiperagudo o agudo, en pacientes presensibilizados; sucede en el postrasplante temprano o en pacientes que desarrollan anticuerpos donante-específicos en el período del postrasplante tardío (51).…”
Section: Complicaciones Del Trasplante Renalunclassified